Genome-Based Metabolic Reconstruction Unravels the Key Role of B12 in Methionine Auxotrophy of an Ortho-Phenylphenol-Degrading Sphingomonas haloaromaticamans - Perruchon, Chiara; Vasileiadis, Sotirios; Papadopoulou, Evangelia S.; Karpouzas, Dimitrios G. (Frontiers in Microbiology, 2020)
Auxotrophy to amino acids and vitamins is a common feature in the bacterial world shaping microbial communities through cross-feeding relations. The amino acid auxotrophy of pollutant-degrading bacteria could hamper their bioremediation potential, however the underlying mechanisms of auxotrophy remain unexplored. We employed genome sequence-based metabolic reconstruction to identify potential mechanisms driving the amino acid auxotrophy of a Sphingomonas haloaromaticamans strain, degrading the fungicide ortho-phenylphenol (OPP) and provided further verification for the identified mechanisms via in vitro bacterial assays. The analysis identified potential gaps in the biosynthesis of isoleucine, phenylalanine and tyrosine, while methionine biosynthesis was potentially effective, relying though in the presence of B12. Supplementation of the bacterium with the four amino acids in all possible combinations rescued its degrading capacity only with methionine. Genome sequence-based metabolic reconstruction and analysis suggested that the bacterium was incapable of de novo biosynthesis of B12 (missing genes for the construction of the corrin ring) but carried a complete salvage pathway for corrinoids uptake from the environment, transmembrane transportation and biosynthesis of B12. In line with this the bacterium maintained its degrading capacity and growth when supplied with environmentally relevant B12 concentrations (i.e. 0.1 ng ml-1). Using genome-based metabolic reconstruction and in vitro testing we unraveled the mechanism driving the auxotrophy of a pesticide-degrading S. haloaromaticamans. Further studies will investigate the corrinoids preferences of S. haloaromaticamans for optimum growth and OPP degradation